2006
DOI: 10.1002/ar.a.20360
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of the rostrum in crocodilians: A comparative analysis using finite‐element modeling

Abstract: This article reports the use of simple beam and finite-element models to investigate the relationship between rostral shape and biomechanical performance in living crocodilians under a range of loading conditions. Load cases corresponded to simple biting, lateral head shaking, and twist feeding behaviors. The six specimens were chosen to reflect, as far as possible, the full range of rostral shape in living crocodilians: a juvenile Caiman crocodilus, subadult Alligator mississippiensis and Crocodylus johnstoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
257
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(272 citation statements)
references
References 42 publications
9
257
1
5
Order By: Relevance
“…Distal stiffening of rostral material could also counteract structural tapering relating to hydrodynamic demands. Previous work has shown that the drag experienced during lateral swiping of the elongate rostrum in alligators is proportional to the height of the jaws (McHenry et al, 2006). Minimizing element height (via distal tapering) may reduce drag in billfish rostra; however, it also comes at the cost of potentially reducing cross-sectional area and resistance to bending (McHenry et al, 2006); distal stiffening of the rostrum may ultimately be a strategy for maintaining adequate flexural stiffness in areas where I is selected to be comparatively low for hydrodynamic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Distal stiffening of rostral material could also counteract structural tapering relating to hydrodynamic demands. Previous work has shown that the drag experienced during lateral swiping of the elongate rostrum in alligators is proportional to the height of the jaws (McHenry et al, 2006). Minimizing element height (via distal tapering) may reduce drag in billfish rostra; however, it also comes at the cost of potentially reducing cross-sectional area and resistance to bending (McHenry et al, 2006); distal stiffening of the rostrum may ultimately be a strategy for maintaining adequate flexural stiffness in areas where I is selected to be comparatively low for hydrodynamic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…FEA provides tools to computationally investigate stress and strain (Daniel and McHenry, 2001; and reaction forces (Porro et al, 2011(Porro et al, , 2013) under a wide range of loading conditions. Researchers have applied this technique to investigate how feeding behavior loads the rostrum in comparative samples of extant crocodylians (McHenry et al, 2006;Pierce et al, 2008), comparing among archosaurs (Rayfield et al, 2007;Rayfield and Milner, 2008), and extinct crocodylomorphs such as thalattosuchians (Pierce et al, 2009). Using multi-body dynamics, Bates and Falkingham (2012) compared estimates of bite force of Tyrannosaurus with estimates from various tetrapods including a large individual of Alligator mississippiensis.…”
Section: Introductionmentioning
confidence: 99%
“…FEA was first applied in many fields of engineering and physics. Its modern application has gone beyond these fields and, nowadays, FEA is used in comparative biomechanics (McHenry et al 2006;Oldfield et al 2012;Walmsley et al 2013), biology (Madzvamuse et al 2003), medicine (Kraft 2012), anthropology (Panagiotopoulou 2009) and geology (Bellian et al 2005). In the field of paleontology, it is used both for bone remains and ichnology (Moreno et al 2007;Arbour et al 2009;Manning et al 2009;Xing et al 2009;Falkingham 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The biggest drawback with FEA is the lack of experimental data (laboratory tests) to define the parameters involved in the model. For this reason, assumptions and simplifications have to be adopted in many cases (McHenry et al 2006). …”
Section: Introductionmentioning
confidence: 99%